An internationalization strategy: How can NOVA- School of Business and Economics attract more Chinese Students? - esteves, Ana Catarina Garcia da Costa Beato (2016)
In the present report I intend to study the Chinese higher education market and Chinese students’ rationales behind the selection of a foreign university, so as to propose simple, feasible, effective measures that will ultimately attract more Chinese students to Nova SBE. In order to do so, it was developed a qualitative research that lead to some interesting highlights, namely the fact that parents have a fairly large influence on the foreign school and country the student chooses. Regarding Nova SBE, the research revealed that Chinese students find courses and professors interesting, but they have difficulties in communicating with locals and claim that the school lacks a systematic, coordinated approach to their integration in the university, something that should start earlier in the process.